Eclectic approach applied to data transformation curriculum course - Moreira, Fernando (2019)
The present society, and in particular the organizations, are currently undergoing a series of metamorphoses of political, economic and social order. These metamorphoses, often referred to in the literature as digital transformation, are due to the rapid and uncontrollable evolution of information technologies and the role they can play in the organizational context. Digital Transformation (DT) is therefore a highly complex and comprehensive enterprise throughout the organization. However, digital transformation alone does not come into any organization for the much-desired success to happen; it is necessary that the information systems, the basis of operation of an organization, are aligned and are part of the same transformation. In this context, organizations have to follow technological developments, update their IS to become agile and innovative so as not to lose competitiveness. Analyzing the scenario of digital transformation, it becomes clear the need for institutions, namely higher education, to offer training to present and future workers in this area. In this paper it is proposed an extension of a curriculum of a course in Digital Transformation in order to accommodate the approach called ECLETIC that aims the use active methodologies in the teaching learning process. The use of the ECLETIC approach is justified by the fact that in addition to a curriculum of any one course must respond to current needs and trends, it should also address the way these skills are acquired, which is why the teaching-learning process is not less important.